2022
DOI: 10.3390/biology11091330
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 and Water Stress in Combination in Plants: Brothers in Arms or Partners in Crime?

Abstract: The changing dynamics in the climate are the primary and important determinants of agriculture productivity. The effects of this changing climate on overall productivity in agriculture can be understood when we study the effects of individual components contributing to the changing climate on plants and crops. Elevated CO2 (eCO2) and drought due to high variability in rainfall is one of the important manifestations of the changing climate. There is a considerable amount of literature that addresses climate eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 87 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…Accordingly, photosynthesis is more sensitive to the combination of soil waterlogging and high temperatures than to individual stressors (Liu et al., 2023). Elevated CO 2 levels have been found to mitigate the adverse effects of water deficit stress on plants, indicating a cooperative effect in safeguarding plants against water stress (Shanker et al., 2022). Additionally, Eucalyptus globulus exposed to a combination of heat and drought stresses triggered a specific protective response not observed when individual stresses were applied (Correia et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, photosynthesis is more sensitive to the combination of soil waterlogging and high temperatures than to individual stressors (Liu et al., 2023). Elevated CO 2 levels have been found to mitigate the adverse effects of water deficit stress on plants, indicating a cooperative effect in safeguarding plants against water stress (Shanker et al., 2022). Additionally, Eucalyptus globulus exposed to a combination of heat and drought stresses triggered a specific protective response not observed when individual stresses were applied (Correia et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The inevitable consequence of stomatal conductance for CO 2 leads to loss of water, affecting the proportion of net photosynthesis to transpiration rate (i.e., transpiration efficiency), as a function of leaf anatomical features that determine the utilization of CO 2 levels in the atmosphere ( Ouyang et al., 2017 ). Under eCO 2 (700 ppm), the imposition of drought stress had less effect on yield attributes than aCO 2 and reduced water use by 10% ( Shanker et al., 2022 ) Similarly, combined eCO 2 and drought stress maintained canopy net photosynthesis by 6−12%. CO 2 supply extended the maintenance of mid-day photosynthesis for a few days, which had an ameliorative effect on rice.…”
Section: Physiological and Molecular Implications Of Combined Abiotic...mentioning
confidence: 99%
“…Significant compromises in yield occur due to the higher respiratory cost of the increased biomass. Night respiration increased by 4–18 mg C hill –1 h –1 in rice genotypes under eCO 2 and HNT at various crop stages before heading ( Shanker et al., 2022 ).…”
Section: Physiological and Molecular Implications Of Combined Abiotic...mentioning
confidence: 99%
“…On the contrary, photosynthesis was more sensitive to the combination of soil waterlogging and high temperature than to the single stresses (Liu et al ., 2023). The literature has also shown that elevated CO 2 has the potential to mitigate the negative effects of water deficit stress on plants, indicating that these two factors act in unison to protect the plant from stress, rather than to exacerbate the situation (Shanker et al ., 2022). On the other hand, in Eucalyptus globulus exposed to a combination of heat and drought stresses, a specific protective response was triggered, which was not activated when either drought or heat stress was applied individually (Correia et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%